TINJAUAN KURVA LAFFER TERHADAP POSISI PAJAK TANGGUHAN PERUSAHAAN DAN PERUBAHAN TARIF PAJAK PENGHASILAN (Studi Empiris pada Perusahaan yang Terdaftar di BEI Periode 2018-2021) - Helen Sophia Siahaan; Endang Kiswara (Diponegoro Journal of Accounting, 2023)
This study aims to examine the impact of tax reform on companies in reported earnings. Chytis revealed that the effect of corporate tax reform on reported earnings and financial position of companies has been extensively recognized in the literature. However, only a few studies that separate deferred tax items to be together with the same disclosure reveal aspects of corporate behavior around the reform. The research was conducted using descriptive analysis method on the company's annual financial statements. Partial least squares (PLS) analysis is used to identify the effect of tax reform (on position tax resilience) which has a significant effect on the company's net profit.The results show that the effect of tax reform on the position of deferred tax assets has a statistically significant effect on the company's net profit.